Ab initio calculation of ICD widths in photoexcited HeNe - Jabbari, Ghazal; Klaiman, Shachar; Chiang, Ying-Chih; Trinter, F.; Jahnke, T.; Gokhberg, Kirill (The journal of chemical physics, 2014)
Excitation of HeNe by synchrotron light just below the frequency of the 1s → 3p transition of isolated He has been recently shown to be followed by resonant interatomic Coulombic decay (ICD). The vibrationally resolved widths of the ICD states were extracted with high precision from the photoion spectra. In this paper, we report the results of ab initio calculations of these widths. We show that interaction between electronic states at about the equilibrium distance of HeNe makes dark states of He accessible for the photoexcitation and subsequent electronic decay. Moreover, the values of the calculated widths are shown to be strongly sensitive to the presence of the non-adiabatic coupling between the electronic states participating in the decay. Therefore, only by considering the complete manifold of interacting decaying electronic states a good agreement between the measured and computed ICD widths can be achieved.
Gesehen am 12.08.2020